Tecnologias analíticas e de produção vegetal de Bauhinia Cheilantha (Bong.) Steud. - Souza, Amilton da Silva (2018)
Bauhinia cheilantha (Bong.) Steud, popularly known as one of the most traditional species in the world, is a species of natural value due to the popular and industrial medicinal use, being a plant of occurrence in the caatinga. This work aimed to demonstrate and analyze analytical techniques and plant production aimed at Bauhinia Cheilantha (Bong.) Steud., As subsidies to strengthen the generation of knowledge aimed at the characterization of the raw material (seed), with potentialities within the context of the Brazilian semi-arid. The fruits and seeds of five matrices of the species, collected in the municipality of Monteiro, Paraíba, were used in the experiment, after which the morphological analyzes (biometry) were carried out, where the diameter, diameter and thickness of 100 fruits were determined. of 100 seeds for each matrix. Plant production was carried out by the planting of 96 seeds of each matrix, characterizing the seedlings since their emergence, development, and withdrawal. The physical-chemical analyzes of the seeds were carried out by conventional techniques (moisture content and ash), and by thermoanalytical techniques, TG and DTA, in different grain sizes, and then the kinetic parameters were evaluated. The results of the biometric characteristics of the fruits and seeds presented similarity between the matrices, as well as the determination of moisture content and ash of the seeds, which presented similarity between the matrices, presenting percent loss of moisture between 12,34% and 13, 17%, and an ash content, with an average remaining percentage value of matter of 3%. In the inert and oxidative atmosphere, the TG curves presented five mass degradation events, where the main step was observed in the second event, with respective temperature and mass loss ranging between 225 - 452°C and 29 - 48% inert atmosphere , and 237-417°C and 29-43% oxidative, for all ratios. The DTA curves by GT showed two exothermic events in the temperature ranges between 274°C - 408°C and 427°C - 582°C, and the peak ranging between 336 - 345°C and 462 - 486°C, respectively first and second event, and DTA by GP curves showed variations in the number of peaks, with one or two events, with an endothermic characteristic. The results of plant production, four matrices presented approximate percentages of PE between 78.1% and 80,2%, except M5 with EP = 64,4%. Seedlings presented a high mortality rate with less than 60 emerged days, presenting a mean percentage value of 92,7% mortality, obtaining the characterization of the seedlings only at 30 and 60 days, respectively, with mean height values of 2,7cm and 3,4cm and of diameter of the stem equal to 0,66mm and 0,77mm, with the retirement of the seedlings, with 60 days, was obtained average value of 5,8g of the mass of the seedlings. It can be concluded that M5 presented a better performance of this study, through data correlation, with better seedling development, so the present study has great importance for the species, considering the presented results and their correlations, bringing information about characteristics physical and thermal characteristics of the seeds, and on the development of this species native to the caatinga.